Sustainable intensification of sugarcane production under irrigation systems, considering climate interactions and agricultural efficiency - Cardozo, Nilceu Piffer [UNESP]; de Oliveira Bordonal, Ricardo; La Scala, Newton [UNESP] (Elsevier, 2018)
Irrigation has been mentioned as one of the main strategies to increase sugarcane yield, but the challenge is how to make this opportunity in an environmentally compatible manner. The aim of this work is to assess the impacts of irrigation systems on sugarcane production not only from an agricultural point of view, but also from a perspective of the efficient use of land and water. Sugarcane yields under rainfed and irrigated conditions were simulated by a calibrated FAO Agroecological Zone Model over a 32-year period (1982–2013) across different Brazilian regions. As expected, higher yields were found for all regions under irrigated systems, but significant variations in terms of yield gains were observed amongst regions. While Petrolina showed the lowest yields (37.5 Mg ha−1) and Ribeirao Preto the highest ones (88.7 Mg ha−1) under rainfed conditions, the results were completely opposite in relation to irrigation scenarios. Petrolina showed the highest response to water supply (167.8 Mg ha−1), while Ribeirao Preto was less responsive to irrigation (145.7 Mg ha−1). The total water consumption or the efficiency of irrigation system is as important as the potential of each region to transform it into biomass, which is attributable to the high levels of solar radiation, photoperiod and air temperature. The data obtained herein highlight that irrigation systems reduced the inter-annual variability of yield (from 20% to 6%) and the land demand for sugarcane production (up to 78%), thus improving the water use and its efficiency (more biomass, less water). These findings provide new insights to decision makers in developing management strategies to further enhance the potential of sugarcane production when judiciously managed with irrigation in regions under low availability of water and high solar radiation and air temperatures.
Keywords: Crop modeling; Land use; Saccharum spp; Sustainability; Water-use efficiency; Yield improvements